Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{\left(\dfrac{1}{32}\right)^{-\frac{1}{5}} = \left(\dfrac{32}{1}\right)^{\frac{1}{5}} = \sqrt[5]{32} = \sqrt[5]{2^5} = 2}[/tex]
[tex]\boxed{\boxed{\mathsf{\left(\dfrac{1}{32}\right)^{-\frac{1}{5}} = 2}}}[/tex]
Resposta:
Explicação passo a passo:
Temos que
[tex](\frac{1}{32})^{-\frac{1}{5}}=>\frac{1}{(\frac{1}{32})^{\frac{1}{5}}}=>\frac{1}{\sqrt[5]{\frac{1}{32}}}=>\frac{1}{\frac{1}{2}}=1.\frac{2}{1}=2.[/tex]
Bons estudos